An analysis of signs in Thao Suranaree Worship Dance on the Occasion of the 555th Anniversary of Nakhon Ratchasima - Nirantechaphat, Wachirarat (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: The Thao Suranaree (Lady Mo) worship dance serves as a social sign, manifesting the devout faith of Nakhon Ratchasima women. The event, scheduled annually on March 23rd, takes on special significance in the year 2023, especially commemorating the 555th anniversary of the city of Nakhon Ratchasima. Organizers have orchestrated 10,555 female dancers for the ritual. Moreover, they have meticulously curated the lyrical content, dance movements, and musical arrangements to harmonize with the performance. The research, entitled "An analysis of signs in Thao Suranaree Worship Dance on the Occasion of the 555th Anniversary of Nakhon Ratchasima" is qualitative research aimed at analyzing signs and signification in the Thao Suranaree (Lady Mo) worship dance. Methodology: The data selected for analysis were purposively sampled and consisted of 7 worship songs and 2 worship dance rehearsal clips produced by the Nakhon Ratchasima Provincial Red Cross Chapter. The research will focus on the lyrical content paired with dance movements communicated by two dance practice participants. These demonstration clips aim to facilitate convenient self-practice for the dancers according to their preferences, including both rear-view dance postures and mirror-facing rehearsal for dance movements. These materials were broadcast on YouTube for dance practice. Results: The results reveal that the signs conveyed in the content of the songs and dance rehearsal clips serve the purpose of communicating the power of Nakhon Ratchasima province, highlighting aspects of the local potential. Additionally, these signs reflect strict adherence to the Thao Suranaree worship dance. They are also employed to demonstrate loyalty to Thao Suranaree, the historical heroine who rescued Nakhon Ratchasima, as depicted in the song's content during significant occasions. In terms of Semiotics, the rehearsal clips convey both denotative and connotative meanings through gestures in the dance format, with the complexity varying based on the intricacy of the theme of the historical story expressed through the songs. In this context, the content of the songs and dance movements is intricately related to the melody and elements of the song. Conclusion: This research contributes to the guidelines for developing semiotic knowledge in the analysis of Thao Suranaree Worship Dance and adds to the application in interdisciplinary studies related to the socio-cultural aspects of the local community.